Femoral head ostectomy for the treatment of acetabular fracture and coxofemoral joint luxation in a Potbelly pig. Issue 2 (19th December 2016) - Smith, Joe S.; Chigerwe, Munashe; Kanipe, Carly; Gray, Sarah
Abstract: Objective: To report the successful surgical treatment of a comminuted left acetabular fracture, a dorsally luxated left femoral head, and avulsion of the ligament of the femoral head by femoral head ostectomy (FHO) and physical therapy in a companion Potbelly pig. Study Design: Case report. Animals: A 1‐year‐old, 13 kg, castrated male, companion Potbelly pig. Methods: The pig presented with a nonweight bearing left pelvic limb lameness of 3 weeks' duration that was noticed shortly after the pig got caught under a fence. Under general anesthesia a lateral approach was made to the fractured limb. A FHO was performed as described for dogs. Following surgery, a period of physical therapy was initiated based on protocols described for dogs. Results: The canine surgical procedure with the approach modified for pigs was successfully performed in our pig. Following surgery, the pig was comfortable and weight bearing. A physical therapy regimen of supervised activity, stairs, and water therapy was used to rehabilitate the leg, as well as a weight management protocol to maintain ideal body condition. The owner was highly satisfied with the outcome. Telephone follow‐up with the owner at 12 months after surgery revealed no impairment to movement, and the pig was maintaining normal ambulation without lameness. No complications were observed with this case. Conclusion: FHO, as described for dogs, provided a favorable outcome for hip luxation caused by acetabular fracture, luxation, and avulsion of the femoral head ligament in this small size Potbelly pig.